Analisis Hubungan Keterdedahan Media dengan Partisipasi Berpolitik Mahasiswa pada Program Indonesia Lawyers Club di TV One (Kasus Mahasiswa Ilmu Politik Insitut Ilmu Sosial dan Ilmu Politik Jakarta) - Siti Nurlailatul Pajriah; David Rizar Nugroho; Feri Ferdinan Alamsyah (Jurnal Penelitian Sosial Ilmu Komunikasi, 2019)
AbstractAnalysis of Media Dependency Relations with Student Political Participation at the Indonesian Lawyers Club Program on Tv One" (Case of Political Science Students of the Jakarta Institute of Social and Political Sciences). Communication Studies Program Broadcasting Concentration, Faculty of Social and Cultural Sciences (FISIB) Pakuan University Bogor. Supervised by Dr. David Rizar Nugroho M.Si. The objectives of the study were (1) Analyzing how students were exposed to the Indonesia Lawyers Club program on Tv One, (2) Analyzing how the political participation of students in Indonesia Lawyers Club program on Tv One, (3) Analyzing the relationship between Indonesia Lawyers Club program on Tv One and political participation of students. This research is a quantitative that produces statistical data using quantitative descriptive methods. Data used questionnaire method or questionnaire and literature study. The population and sample in this study were political science students from the Jakarta Institute of Social and Political Sciences who had watched Indonesia Lawyers Club on Tv One with accidental sampling. The research instrument tested the validity of the Pearson Product Moment reliability with Cronbach's Alpha. Data analyzed technique used is the average score and correlation test. The results show that: (1) In the media discontinuation variable the duration indicator of the majority of respondents watching Indonesia Lawyers Club 10-20 minutes in one watch. (2) Indicator of frequency of watching Indonesian Lawyers Club, the majority of respondents watch twice a month. (3) There is a significant relationship between media exposure and student political participation which is obtained by Pearson Product Moment correlation test for ratio, interval and ordinal data.Keywords: media dependency, political participation, relationships